Hyperhydration with cisplatin does not influence pemetrexed exposure. Issue 2 (26th August 2021) - de Rouw, Nikki; Derijks, Hieronymus J.; Hilbrands, Luuk B.; Boosman, René J.; Piet, Berber; Koolen, Stijn L. W.; Burgers, Jacobus A.; Dingemans, Anne‐Marie C.; van den Heuvel, Michel M.; Hendriks, Lizza E. L.; Aerts, Joachim G. J. V.; Croes, Sander; et al.
Abstract : Pemetrexed is a cytotoxic drug for first‐line treatment of lung cancer. It is often combined with other anticancer drugs such as cisplatin or carboplatin. In clinical practice, hyperhydration regimens are applied to overcome cisplatin‐related nephrotoxicity. As pemetrexed is almost completely eliminated from the body by the kidneys, hyperhydration can result in augmented clearance. Furthermore, administration of large quantities of fluid may increase the volume of distribution of pemetrexed. Pharmacokinetics and, thus, efficacy and toxicity may be influenced by hyperhydration. This has not yet been properly studied. We performed a population pharmacokinetic analysis to assess hyperhydration as a covariate for pemetrexed clearance and for volume of distribution A relevant change was defined as >25% increase in clearance or volume of distribution. In our extensive dataset of 133 individuals, we found that hyperhydration did not significantly or relevantly explain variability in pemetrexed clearance (unchanged, P = .196) or volume of distribution (+7% change, P = .002), despite a power of >99% to detect a relevant change. Therefore, dose adjustments of pemetrexed are not required during hyperhydration with cisplatin.